(untitled) (Acta Medica Academica, 2010)
R. P. Bentall is Professor of Clinical Psychology at the Universityof Bangor in Wales (UK). He has published extensively in the field ofthe causes and treatment of severe mental illnesses. His previous book,“Madness Explained: Psychosis and Human Nature”, won the BritishPsychological Society Book Award for 2004.